2020
DOI: 10.1073/pnas.2010761117
|View full text |Cite
|
Sign up to set email alerts
|

Mycena genomes resolve the evolution of fungal bioluminescence

Abstract: Mushroom-forming fungi in the order Agaricales represent an independent origin of bioluminescence in the tree of life; yet the diversity, evolutionary history, and timing of the origin of fungal luciferases remain elusive. We sequenced the genomes and transcriptomes of five bonnet mushroom species (Mycena spp.), a diverse lineage comprising the majority of bioluminescent fungi. Two species with haploid genome assemblies ∼150 Mb are among the largest in Agaricales, and we found that a variety of repeats between… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 99 publications
2
39
0
3
Order By: Relevance
“…S3). For uniformity in downstream analyses, we reanalysed data from former studies (Almási et al, 2019;Gehrmann et al, 2018;Ke et al, 2020;Krizsán et al, 2019;Liu et al, 2018;Sipos et al, 2017), yielding data for eight species in the order Agaricales, which comprises a single origin of complex fruiting body morphologies (Marisol et al, 2020;Varga et al, 2019). P. ostreatus and Pt.…”
Section: Overview Of New Rna-seq Datamentioning
confidence: 99%
“…S3). For uniformity in downstream analyses, we reanalysed data from former studies (Almási et al, 2019;Gehrmann et al, 2018;Ke et al, 2020;Krizsán et al, 2019;Liu et al, 2018;Sipos et al, 2017), yielding data for eight species in the order Agaricales, which comprises a single origin of complex fruiting body morphologies (Marisol et al, 2020;Varga et al, 2019). P. ostreatus and Pt.…”
Section: Overview Of New Rna-seq Datamentioning
confidence: 99%
“…Luciferase is reported to originate in Agaricales, and it is currently detectable in Armillaria and Mycene species. 3-hydroxyhispidin, the hydroxylated hispidin, is the luciferine [251]. To note, the different effects of prolactine (PRL) and c-aminobutyric acid (GABA); respectively negative and positive common effects of amelanocyte-stimulating hormone (a-MSH) and melatonin (Mt); almost uninfluential effects of nitric oxide (NO).…”
Section: Bioluminescencementioning
confidence: 99%
“…Luciferase is reported to originate in Agaricales, and it is currently detectable in Armillaria and Mycene species. 3-hydroxyhispidin, the hydroxylated hispidin, is the luciferine [251].…”
Section: Bioluminescencementioning
confidence: 99%
“…S2 ) 8 . The presence of both luminous and nonluminous species in a single genus is likely widespread, but only a few examples have been confirmed; for example, the genera Vibrio and Photobacterium (marine bacteria) 9 , Epigonus (deep-sea fishes) 10 , Mycena (bonnet mushrooms) 11 and Eisenia (terrestrial earthworms) 12 have been reported to contain both luminous and nonluminous species. P. litoralis and P. longissimus can easily be collected at the same beach 8 and reared in a laboratory; thus, they are suitable for studying the ecology and evolution of bioluminescence.…”
Section: Discussionmentioning
confidence: 99%